Analisis Fungsi dan Estetika Logo ‘Nyenyes’ Palembang - Patriansah, Mukhsin; Viatra, Aji Windu; Yazid, Iqbal Maulana (Sosial Budaya, 2025)
A logo as a visual identity contains design elements as symbols to represent the values, goals and characteristics of the entity being represented. The thing behind the interest of the author of this research is the use of the word "Nyenyes" in the logo being studied. The main problem raised in this research is the design principles of the Nyeyes Palembang logo, viewed from functional and aesthetic aspects. The problem solving plan begins by using qualitative research methods with a measurable and systematic analysis process, starting from the logo description stage, logo analysis by looking at relationships and relevance, as well as function and aesthetic studies based on design principles such as simplicity, timeless, balance, proportional and relevant. Thus, the results of the research can be seen from the visual appearance of the Nyenyes Palembang logo which has implemented design principles as a whole, so that the effectiveness and efficiency values of the logo are very visible and have relevance to the culture of the people of Palembang city. The results of the analysis are strengthened by questionnaire data that the author collected, from a total of 50 correspondences, more than 70% stated that the Nyenyes Palembang logo as a visual identity was attractive, effective and efficient in conveying messages to the target audience.